PROTECTION AND LAW ENFORCEMENT OF VICTIMS OF ACCOUNTING AND BANKING CRIMES - Herman Fikri (Saburai International Journal of Social Sciences and Development, 2017)
This paper will discuss main causes and precaution of banking and accounting crimes that can be minimized by public accountant. The Public Accountants have a very important role, especially in improving the quality and credibility of information relating to financial or financial statements of a particular entity. In the Regulation No. 5 of 2011 it is quite clear that the profession of Public Accountants has a big role in supporting a healthy and efficient national economy and improving the transparency and quality of information in the field of finance, particularly for the interests of Banking and society. Frequently the occurrence of banking and accounting scandals as political and business scandals that come with the disclosure of the bad behavior of the of public company executives. These crimes typically involve complex methods of misusing or misleading funds, exaggerating incomes, minimizing costs, exaggerating the corporate asset value or reducing the liabilities in the reporting, sometimes they also collaborate with officials in other companies or in their affiliates. If it refers to the notion of banking and accounting scandals mentioned above, banking and accounting crimes tend to be closer to the term of fraudulent statement (fraud regarding the presentation of financial statements) for the sake of interest. Therefore, The emergence of Public Accountant services need to increase, specifically the quality of financial information which is used as one of the considerations in decision making in particular in giving credit to customers (debtors). Thus, Public Accountants need to continually improve the competence and professionalism in order to meet the needs of service users and carry public trust.